Pengaruh Penambahan Tepung Daun Katuk Terhadap Kualitas Organoleptik dan Fisik Roti Tawar - Almira Salsabila; Rivana Agustin; Titik Budiati (Politeknik Negeri Jember, 2022)
The addition of katuk leaves in the process of making white bread aims to determine the effect of adding katuk leaves to consumer organoleptic results. The research methodology is a field study which includes observations and interviews. The results obtained are the proportion of katuk leaf flour in the manufacture of katuk leaf bread has an effect on the organoleptic results of color, taste, appearance, texture, aroma, expansion power, and specific volume of katuk leaf bread. The results of organoleptic color, taste, appearance, texture, aroma that were most preferred by respondents were plain bread with the addition of katuk leaf flour as much as 5%. Addition of more than 5% katuk leaf flour produces doughy and non-fluffy bread.